(3TaGA GdZdjd aj Yde GdNdjds - (3eMeO Hf eMeO GdSaGbSjs; (3GHf GdMGLH , LeGd GdOjf CHh YeQh GHf GdMGLH, LeGd GdOjf CHh YeQh GHf GdMGLH,J (B646 (3g` s ((3YHOGdQMef Hf CHj HcQ Hf CMeO GdfaRj s)
(3ChdgG (B:s
(3jHOC HGdHGH GdSGHY aj GdoeYGbHI hGdeQGbHI hGdecGfaI s
(3BNQgG (B:s
(3aEf NdG Chd HjJ aj GdbUjOI ef GdJUQjY hGdJabjg agh GdeUeJ hgPG oefJgi Gdbhd aj GdcJGH hGddg Gdoehab ddUhGH s
(3GdfSNI HgG MhGTs
(3Hg ebGHdI aj BNQgGs
(3fSNI QGHYI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdYQhV hGdbhGais